2014
DOI: 10.1111/papr.12265
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Analgesic Effect by Combination of Non‐Noxious Stimulation and Noxious Stimulation in Humans

Abstract: The aim of the this study was to investigate the combined effects of heterosegmental non-noxious and noxious stimulation on electrically induced tooth pain. The late component of somatosensory-evoked potentials (SEP), induced by electrical tooth stimulation and pain intensity, were examined under electrical stimulation to forearms. Noxious, non-noxious, and combined non-noxious and noxious electrical stimulation were applied to median nerves on the forearms. Four experimental sessions (ie, control session, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…A previous study had shown that a combination of non-noxious and noxious stimuli had a potent analgesic effect on tooth pain (13). The present findings support this previous observation, and suggest that the potent analgesic effect of combined non-noxious and noxious stimuli is elicited by segmental control and an activated central mechanism, including the endogenous opioid and descending pain inhibitory pathways (23) (Le Bars D et al, Opioids and diffuse noxious inhibitory control Fig.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A previous study had shown that a combination of non-noxious and noxious stimuli had a potent analgesic effect on tooth pain (13). The present findings support this previous observation, and suggest that the potent analgesic effect of combined non-noxious and noxious stimuli is elicited by segmental control and an activated central mechanism, including the endogenous opioid and descending pain inhibitory pathways (23) (Le Bars D et al, Opioids and diffuse noxious inhibitory control Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The patients comprised 21 males and 23 females aged between 20 and 34 years, with a mean age of 26.3 ± 6.36 years (± SD) (Table1). As in the previous study (13), the 44 patients were randomly allocated to four groups, each comprising 11 patients: noxious stimuli (CPM), non-noxious stimuli (TENS), combined noxious and non-noxious stimuli (combined), and a sham group. Chi-squared test revealed no significant inter-group differences in gender ratio.…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations